2022
DOI: 10.1371/journal.pone.0269026
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of COVID-19 patients in Bali, Indonesia

Abstract: Introduction The spectrum of illness and outcomes of coronavirus disease 2019 (COVID-19) patients may vary. This study reports the characteristics of COVID-19 patients in Bali, Indonesia, and evaluates the diagnostic value of their clinical symptoms. Method This observational study was conducted in eight hospitals. The patients were classified as non-severe COVID-19, severe COVID-19, and non-COVID-19. Demographics, clinical, laboratory, and radiologic characteristics, and outcomes of COVID-19 patients were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Previous research has shown a correlation between anosmia and mortality in COVID-19 patients ( p =0.019) [ 19 ]. A study conducted in Bali, Indonesia [ 20 ] also found a link between anosmia and death in COVID-19 patients. Prior research confirmed a significant association between anosmia and dyspnea and mortality in patients with COVID-19 [ 21 ].…”
Section: Discussionmentioning
confidence: 98%
“…Previous research has shown a correlation between anosmia and mortality in COVID-19 patients ( p =0.019) [ 19 ]. A study conducted in Bali, Indonesia [ 20 ] also found a link between anosmia and death in COVID-19 patients. Prior research confirmed a significant association between anosmia and dyspnea and mortality in patients with COVID-19 [ 21 ].…”
Section: Discussionmentioning
confidence: 98%
“…Similar results were found in several studies where hyperglycemia was associated with adverse conditions in COVID-19, both with comorbid DM and no comorbid DM. [31]In the case group, 75% (24 cases) of patients with hyperglycemia died, and 25% (8 cases) lived. While in cases without hyperglycemia, 64 cases (68%) lived, and 30 cases (31.9%) died.…”
Section: International Journal Of Scientific Advances Issn: 2708-7972mentioning
confidence: 99%
“…The FDA authorized chloroquine sulfate and hydroxychloroquine sulfate as first-line treatments on the basis of early clinical studies. However, antiviral medications including molnupiravir, remdesivir, and kaletra (a combination medicine of lopinavir and ritonavir) have also been proposed to help COVID-19 sufferers feel better [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%